Discovery of an orally bioavailable NK1 receptor antagonist, (2S,3S)-(2-methoxy-5-tetrazol-1-ylbenzyl)(2-phenylpiperidin-3-yl)amine (GR203040), with potent antiemetic activity. - Ward, P; Armour, DR; Bays, D; Evans, B; Giblin, G; Heron, N; Hubbard, T; Liang, K; Middlemiss, D; Mordaunt, J (1995)
The antiemetic, pharmacokinetic, and metabolic profile of CP-99,994, a potent NK1 receptor antagonist, has been carefully evaluated. As a result we began a medicinal chemistry program which initially identified a 3-furanyl analogue (6) with improved antiemetic potency and a methyl sulfone (5) with enhanced metabolic stability and oral bioavailability. The improved pharmacokinetic profile of methyl sulfone (5) was associated with its low lipophilicity, and a therefore a number of heterocyclic analogues with reduced log D were synthesized. Out of this program emerged 19 (GR203040), a tetrazolyl-substituted analogue. Tetrazole 19 inhibits radiation-induced emesis in the ferret with high potency when administered both subcutaneously and orally, has a long duration of action, and has high oral bioavailability in the dog. Tetrazole 19 is currently undergoing evaluation as a novel approach for the control of emesis associated with, for example, cancer chemotherapy.